Building Integrated Knowledge and Developing Student Character in Civic Education Learning - Aisa Abas; Louisa Metekohy; M. S Sapulette (CV. Rayyan Dwi Bharata, 2023)
Organizing learning for teachers who have the role of designing or designing learning, carrying out learning, and assessing learning in carrying out assignments is required not only to seek intellectual abilities/intelligence, skills, but also to have good character behavior attitudes. Likewise in learning Citizenship Education (Civics) from these needs this research was conducted to describe building integrated knowledge to develop the character of students in learning Citizenship Education. This research was conducted at SMA Negeri 27, Leihitu District, Central Maluku Regency. Sampling technique using snowball sampling Data collection techniques using observation, interviews, and documentation. The results of the research revealed that the process of building integrated knowledge developing character is applied in teacher activities using trigger questions asking moral experiences to connect students with learning material, conducting studies of subject matter by presenting problems in society, events that occur in society, local community culture, customary values -moral values in society. Obstacles faced by the ability of teachers who only focus on understanding the management of learning on knowledge of the material being studied and have not been solidly integrated for developing student character, the use of learning resources still depends on the teacher has not varied for students to find and practice character, and the hours of Civics lessons are limited. Learning efforts are carried out using problems that occur in society, local wisdom culture, moral values that have become customary in the community in facilitating studies to serve learning in finding material information and making students discover the characters that must be possessed from their environment.